Sintaksis Kata soal Argumen Bahasa Mendriq: Kerangka Minimalis (Jurnal Bahasa, 2010)
In general, there appear to be three major patterns with regard to the position of wh-question words. The first pattern is that they move to the beginning of a sentence and form the scope of the sentence in which the question occur. The second pattern is to remain in the same position in which the answer would occur, a phenomenon widely referred to as wh in-situ. The third pattern is that they may move to the middle of a sentence, this is known as partially moved wh. Mendriq, a language spoken by a small number of aborigines in the East Malaysia, instantiates the first two patterns, moved wh and in-situ wh, in the same sentence. This phenomenon is evident in the two wh-question, naken "who" and luk ai or alow "what", which are referred to as argument questions in this paper. We claim that these wh-questions are not only in-situ wh-questions but also exhibit movement. Chomsky (1993) proposed that the [Q]-feature of C is strong in all languages. In addition, Adger (2003) proposed that the strong [Q]-feature also has a strong uninterpretable feature [uwh] on C, which causes the wh to move to the scope position, Spec CP, to check the feature locally. Keeping Chomsky's claim and observing Adger's suggestion, writers propose that the in-situ and the moved phenomena are due to the empty Op which has a [wh]-feature on both wh-questions in this language. The Op may move to Spec CP to check locally the [uwh] which causes the argument questions to remain in situ or the argument questions may move optionality to the Spec CP before Spell Out to check the strong [uwh]-feature locally atthe Spec CP.Keywords: Syntax, wh-question words, argument, Mendriq language,what, who